Do tax administrative interventions targeted at small businesses improve tax compliance and revenue collection? Evidence from Ugandan administrative tax data - Jouste, Maria; Nalukwago, Milly I.; Waiswa, Ronald (WIDER Working Paper, 2021)
This paper conducts an impact evaluation of the effects of two tax administration interventions-a taxpayer register expansion and education programme, and a new electronic filing system for presumptive tax-on the number of small business taxpayers and presumptive tax revenues in Uganda. Using a difference-in-differences approach and administrative data covering both presumptive taxpayers and comparable small corporate income taxpayers, we find that the number of small business taxpayers filing tax returns and presumptive tax revenues increased substantially after the interventions. We argue that the interventions complement each other because both interventions were established around the same years, and the taxpayer register expansion programme focused on not only registering but also educating taxpayers with regard to tax compliance. We analyse the cost-effectiveness of the taxpayer register expansion programme and find that the benefits outweigh the costs.